2015
DOI: 10.1073/pnas.1507441112
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of formation of coffinite, USiO 4

Abstract: Coffinite, USiO 4 , is an important U(IV) mineral, but its thermodynamic properties are not well-constrained. In this work, two different coffinite samples were synthesized under hydrothermal conditions and purified from a mixture of products. The enthalpy of formation was obtained by high-temperature oxide melt solution calorimetry. Coffinite is energetically metastable with respect to a mixture of UO 2 (uraninite) and SiO 2 (quartz) by 25.6 ± 3.9 kJ/mol. Its standard enthalpy of formation from the elements a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
107
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(121 citation statements)
references
References 48 publications
(97 reference statements)
13
107
0
Order By: Relevance
“…Acquired data were processed with the Calisto software package from AKTS. Detailed procedures have been described previously [11,22].…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acquired data were processed with the Calisto software package from AKTS. Detailed procedures have been described previously [11,22].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Flushing oxygen gas at ~ 50 mL/min through the calorimeter chamber assisted in maintaining a constant gas environment above the solvent [25]. Dissolution of uranium oxides and other uranium-containing compounds as U 6+ species has been demonstrated in this solvent, and their drop solution enthalpy data were obtained previously [10,11,22,[26][27][28]. Upon rapid and complete dissolution of the sample, the enthalpy of drop solution, ΔH ds , was obtained.…”
Section: High Temperature Oxide Melt Solution Calorimetrymentioning
confidence: 99%
“…Motor activity can enhance network elasticity 61,68,138,227,238 , which may stabilize networks against motor-induced fracture. Furthermore, at high loads, muscle and non-muscle myosin II motors exhibit catch bond behavior [239][240][241] . Boundary adhesion may also need to be overcome.…”
Section: Failure Percolation and Global Contraction (Iii)mentioning
confidence: 99%
“…Moreover, many myosins (skeletal muscle, smooth muscle, and non-muscle myosin IIB) exhibit catch bond behavior. Singlemolecule measurements with optical tweezers showed that the binding affinity of myosin motors to actin increases with applied force, for forces up to ~6 pN 239,240,335 . This catchbond behavior may promote contractility 336 .…”
Section: Interplay Between Motor Activity and Connectivitymentioning
confidence: 99%
“…Uraninite is capable of retaining the imprints of the earlier magmatic event and capturing the footprints of subsequent hydrothermal events [18,19]. On the other hand, recent researches suggest that mobilized U can be subsequently reprecipitated as coffinite during later silica-rich fluid circulation events [10,20]. Accordingly, the evolution of U mineral generations is instructive for understanding U circulation from magmatic to hydrothermal stages during pegmatite development.…”
Section: Introductionmentioning
confidence: 99%